Implementasi Kebijakan Pemerintah Kota Denpasar dalam Pengendalian Parkir Liar Guna Mendukung Ketertiban Lalu Lintas - Pande Gede Mantra Artha Wicaksana; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Warmadewa Press, 2022)
Local Charges One source of local revenue is parking fees on the edge of ordinary streets. In its implementation, parking fees are often used by several people without permission to make illegal parking spaces. Based on this there are two, the purpose of the study is to find out the legal actions of the city government with Denpasar based on the authority to issue illegal parking on the road as well as the factors that hinder and in the issuance of illegal parking on the road. The main problems studied are how to implement Denpasar City Regulation Number 19 of 2011 to support traffic order, what factors affect the process of controlling illegal parking and the government's efforts to minimize congestion in Denpasar City. This study uses empirical legal study methods. The results of this study indicate that so far with the implementation of the implementation of Regional Regulation No. 19 of 2011 it is clearly sufficient in creating Traffic Order in the Parking Area Area in Denpasar City, so that congestion can be overcome and traffic accidents can be prevented. However, there are still several factors that influence the control of illegal parking, but various efforts have been made, such as controlling roads and managing parking areas, conducting vehicle raids, issuing warning letters or taking action, as well as conducting counseling and supervision.